The Nurse as the Patient's Advocate: A Contrarian View - Shannon, Sarah E. (The Hastings Center report, 2016)
An important role for all health care professionals is to be an advocate for their patients, and there is no question that many patients need advocacy to reach their health care goals. The role of advocate takes many forms, but one is to speak up when one is concerned for the safety or well-being of a patient. A nurse is often the member of a health care team most likely to notice changes that might signal problems or poor responses to treatment. The duty of the nurse is to speak up in a timely and urgent manner when the nurse believes—or fears—that the patient's safety may be at risk. Yet the role of nurses as advocates for their patients has assumed near-mythic status. Rather than seeing advocate as one among many equally important and interrelated professional roles, the nurse, when asked, “Who are you?” is likely to give the heartfelt and passionate answer, “The patient's advocate!” This essay examines and critically analyzes the advocacy role adopted by the nursing profession and outlines the challenges it has created to nursing's contributions to collaborative practice, ethics, and policy in health care.